Analysis of Financial Literacy of Students Receiving KIP Scholarships in Universitas Muhammadiyah Surakarta - Hartanti, Adelita Putri; Wahyudi, Tri Nur (Proceedings International Conference on Education Innovation and Social Science, 2023)
Students as the millennial generation will encounter increasing complexity in terms of goods, services, and the financial sector. The source of student finance in this research is scholarships. The KIP (Kartu Indonesia Pintar) program in tertiary institutions also aims to break the cycle of financial limitations among economically disadvantaged families, and reduce unemployment in the future. This research will focus on students' understanding of financial literacy, then this research also aims to explore the role of financial literacy in the financial management of students receiving KIP college scholarships and the factors that influence them to implement financial literacy. This type of research is a qualitative research with an ethnographic design. Data collection techniques were carried out using interviews, observation, and documentation. The data analysis technique used in this research is using steps consisting of four activities, namely data collection, data reduction, data display, verification and confirmation of conclusions. The results showed that the understanding of financial literacy and the role of financial literacy in the financial management of KIP recipient students at the Universitas Muhammadiyah Surakarta was classified as very good and was in the Well Literate category. Then this study also shows that the factors that influence financial literacy are technological factors, parents' income, age, gender, and parents' educational level.